Digital transformation of archival system: optimizing storage efficiency in administrative processes for Islamic senior high schools - Nur Wahid; Lutfi Wakhid (JPP (Jurnal Pendidikan dan Pembelajaran), 2025)
This research aims to analyze the impact of archive digitization on the efficiency of storage space and management of administrative documents. The method used is a qualitative descriptive case study at Madrasah Aliyah Negeri 2 Banyuwangi, including direct observation, interviews with archive managers, and data analysis before and after the implementation of digitization. The results indicated that implementing the digital system succeeded in reducing the need for physical storage space by 80%, with important documents that must be in physical form still stored in an organized manner. In addition, the implemented cloud-based system allows for safer, faster, and more cost-effective archive management. Digitization not only improves efficiency but also supports space optimization for other purposes and the institution's embrace of the modern technological era. This research concludes that digitizing archive systems is an effective solution to overcome space constraints and improve the quality of administrative management in educational institutions.